2018
DOI: 10.1590/1982-021620182064218
|View full text |Cite
|
Sign up to set email alerts
|

Osmolality analysis of human milk and an infant formula with modified viscosity for use in infants with dysphagia

Abstract: Purpose: to evaluate the effects of a thickening agent on the osmolality of human milk and on an infant formula, with respect to concentration and time. Methods: six trials were performed to evaluate the osmolality of a natural and thickened infant formula, raw human milk, and pasteurized human milk. Rice cereal was used as a thickening agent (at concentrations of 2%, 3%, 5%, and 7%). Osmolality was measured using the Advanced Micro Osmometer Model 3300 after sample preparation periods of 0-60 minutes. Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We found that intake of contrast affected the fecal score and increased the transit time, indicating that the contrast solution itself may affect the total transit time. The osmolarity of the solution used in this study was 290 mOsm/L (unpublished observations) and therefore comparable to mother's milk (277-303 mOsm/l (31). Its chemical carrier constituents include mainly calcium and sodium which should not have notable direct gut osmotic effects or increase the fecal score, although such effects cannot be excluded (32).…”
Section: Discussionmentioning
confidence: 86%
“…We found that intake of contrast affected the fecal score and increased the transit time, indicating that the contrast solution itself may affect the total transit time. The osmolarity of the solution used in this study was 290 mOsm/L (unpublished observations) and therefore comparable to mother's milk (277-303 mOsm/l (31). Its chemical carrier constituents include mainly calcium and sodium which should not have notable direct gut osmotic effects or increase the fecal score, although such effects cannot be excluded (32).…”
Section: Discussionmentioning
confidence: 86%